La femme-frontière : Desert Blood comme paradigme de la violence engendrée par l’exil statique dans la société chicana - Stéphanie Benson; Caroline Lepage (Les Cahiers ALHIM)
Experiences of exile are certainly as unique as the violence they give rise to, depending on the situation and the place... The case of Desert Blood, by the Chicana author Alicia Gaspar de Alba is particularly interesting from this point of view in that it takes into account a very special kind of exile — static exile engendered by a brutal historical displacement of the Mexican-U.S. border — and a particular use of violence, since it addresses the terrible femicide in which women have been killed from the 1990s up until today in the unfortunately infamous zone around Ciudad Juarez (the number of victims is now probably into the thousands). This novel is groundbreaking in the sense that, over and beyond its ruthless denunciation and serious accusations, it shows the way towards a new form of borderland collective identity, questioning other levels of individual identity, especially with regard to sex and gender.